Covim : converting vim into a real-time collaborative text editor - Guo, Yang. (2011)
With the advance of computer technology, single-user applications are used pervasive in our daily lives and day-to-day work. Teamwork and collaboration are being more and more emphasized and with the ever-advancing information technology, geographic locations are no longer barriers collaboration across distance but the availability of collaborative applications and platforms.While many techniques are used in the development of collaborative applications, Transparent Adaption and Operational Transformation techniques that emphasize on leveraging existing commercial off-the-shelf single-user applications into collaborative ones without modifying the source code of the adapted application is proven to be successful in producing collaborative applications that can not only achieve real-time concurrent editing but also are most familiarized by users.